Feedbacks and landscape-level vegetation dynamics. (May 2015) - Bowman, David M.J.S.; Perry, George L.W.; Marston, J.B.
Highlights Landscape-level feedbacks are critical for understanding of the risk of rapid switching between ecological states, such as forest and savanna biomes. These feedbacks are difficult to study because the spatial and temporal scales preclude classical experiment approaches. We suggest that identifying and understanding the role of landscape-level feedbacks demands a synthetic approach that blends observational, experimental, model-based approaches, conceptual models, and narratives.